2005
DOI: 10.1007/s11284-005-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

Climatic factors affecting the tree‐ring width of Betula ermanii at the timberline on Mount Norikura, central Japan

Abstract: Takahashi et al. 2Tree-ring width chronology of Betula ermanii was developed at the timberline (2400 m a.s.l.) on Mount Norikura in central Japan, and climatic factors affecting the tree-ring width of B. ermanii were examined. Three monthly climatic data were used for the analysis (i.e., mean temperature, insolation duration, and sum of precipitation). The tree-ring width of B. ermanii was negatively correlated with December and January temperatures and with January precipitation prior to the growth. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 46 publications
(52 reference statements)
7
31
1
3
Order By: Relevance
“…This view was confirmed in our study. Although our results were different from some previous studies that showed positive correlations of tree growth with temperature in the prior winter (Peterson and Peterson 1994;Pederson et al 2004;Fan et al 2009;Liang et al 2010), Takahashi et al (2005) showed that Betula ermanii was negatively correlated with December and January temperatures at the treeline in Japan. As for the negative associations of tree growth with the prior winter temperatures, it is possible that high temperatures could enhance respiration rates, which decreased the storage of the carbohydrate production (Pilcher and Gray 1982).…”
Section: Discussioncontrasting
confidence: 99%
“…This view was confirmed in our study. Although our results were different from some previous studies that showed positive correlations of tree growth with temperature in the prior winter (Peterson and Peterson 1994;Pederson et al 2004;Fan et al 2009;Liang et al 2010), Takahashi et al (2005) showed that Betula ermanii was negatively correlated with December and January temperatures at the treeline in Japan. As for the negative associations of tree growth with the prior winter temperatures, it is possible that high temperatures could enhance respiration rates, which decreased the storage of the carbohydrate production (Pilcher and Gray 1982).…”
Section: Discussioncontrasting
confidence: 99%
“…Tree-ring width is commonly related to climate in both the previous year and current year (Bräuning 1999;Takahashi et al 2005;Savva et al 2006), which was also verified in this study. Generally, TRW was negatively associated with temperatures in the prior winter and the months before the growing season at all elevations (Fig.…”
Section: Discussion Chronology Evaluationsupporting
confidence: 83%
“…Above subalpine coniferous forest, it forms open woodlands of more than 300 m in vertical width, and invades to the uppermost limit of tree growth at nearly 2,100 m a.s.l., providing ideal places and materials for the dendroclimatical study (Wu et al 2009). Unfortunately, such studies on B. ermanii are in a shortage, and most of which were developed at upper tree-lines (Takahashi et al 2005;Yu et al 2005;Yu et al 2007), which could not give a thorough interpreting of the dendroclimatical features of Betula ermanii. With the objective to explore the climatic factors affecting variation in tree-ring growth and to identify whether these factors differ with altitude, we performed a dendroclimatic analysis on Betula ermanii in the northern slope of Changbai Mountain (41°31'-42°28' N, 127°9'-128°55' E).…”
Section: Vol 70 99-107mentioning
confidence: 99%